ESTRATEGIAS DE COMERCIALIZACIÓN DEL SACHA INCHI - Tito Huamani, Pedro L. (2009)
This research has as purpose to develop viable strategies for positioning, marketing the sacha inchi and its derivatives in the market of the big Lima. The Inchi Sacha is a native plant of the peruvian Amazon, first described as a species in 1753 by naturalist Linneo, hence its scientific name Plukenetia volubilis Linneo. In Peru is known of its existence from the empire. Thus, until today has taken different names: Sacha Inchi, quechua word meaning peanut mount; Amui a term used by the aboriginal tribes of the Amazon, and the Inca Peanut. Today, also known as the Inca Peanuts, is the natural oilseed with a higher content of omega, an essential fatty acid for human life. Composed: 48.60% of essential fatty acid alpha linolenic (Omega 3), 36.80% of essential fatty acid alpha linoleic (Omega 6) and 8.28% of oleic acid (omega 9). It also has the lowest content of saturated fatty acids: 6.39% on average, 3.85% of palmitic and 2.54% of stearic. Nowadays the Sacha Inchi is sold at its highest percentage in the basic form, ie, toasted beans (similar to peanuts) which is easily located in most healthy food stores, while supermarkets sell oil, which in stage of industrialization is aimed at a small and selective segment of the population of Lima. The research also shows that we can manufacture and market other products made on the basis of Sacha Inchi. This way, the marketing options are: Inchicapi, chili of sacha inchi, cutacho, sacha inchi butter, inchi cucho, acha inchi tamale, nougat, snack, among others; items in which the city of Lima, is still a captive market to mature. In all, the advertising and promotion strategies should emphasize the nutritional and even healing properties of Sacha Inchi. In this regard, secondary research shows that frequent consumption, reduces obesity and favours the cancer treatment, diabetes, heart disease, blood pressure, erectile dysfunction and stress. Even, there is a research that posits that Sacha Inchi prevent Alzheimer’s, improve vision, improve child development, enhances mental focus and strengthens the immune system.